The Impact Of Organisational Characteristics And Support Mechanism On The Success Of Agricultural Extension Management - Omar, Jadalla A. E. (2013)
Agricultural extension systems in the world are struggling to prove their importance and relevance related to sustainable agricultural development. Thus, the role of agricultural extension is important to support sustainable agricultural development, which is moving from production to a wider set of sustainability and environmental objectives. The purpose of this study is to provide an organizational framework for designing an effective agricultural extension service to support sustainable agricultural development. It also aims to identify major constraints, organizational characteristics and appropriate mechanisms to support sustainable agricultural development using a descriptive-correlative design. This study aims to investigate perceptions among farmers, managers and deputy directors from Eastern part of Libya were selected from major cities of agricultural regions (Tubruq, Derna, Al Bayda, Al Marj, Benghazi and Ajdabiya). A quantitative data analysis approach was used to analyze the data. Data were collected through the use of questionnaires on a sample of the population involved in agriculture in the study area. A total of three hundred and fifty (350) questionnaires were distributed to farmers where 300 responded. Also, fifty (50) questionnaires were distributed in the eastern region of Libya where 25 managers and 21 deputy directors responded. The study found a positive association between organizational characteristics, support mechanisms and the performance of agricultural extension. However, multiple regression analysis found organizational characteristics to be the highest predictor of variables, followed by support mechanisms.